2020
DOI: 10.3399/bjgp20x710933
|View full text |Cite
|
Sign up to set email alerts
|

Reorganisation of primary care for older adults during COVID-19: a cross-sectional database study in the UK

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic has resulted in a rapid change in workload across healthcare systems. Factors related to this adaptation in UK primary care have not yet been examined.AimTo assess the responsiveness and prioritisation of primary care consultation type for older adults during the COVID-19 pandemic.Design and settingA cross-sectional database study examining consultations between 17 February and 10 May 2020 for patients aged ≥65 years, drawn from primary care practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(154 citation statements)
references
References 19 publications
4
140
2
8
Order By: Relevance
“…The cross-sectional RSC study found more remote consulting amongst people in IMD quintile 1 (most deprived). 4 In our longitudinal study, we found no signi cant effect of deprivation on the change in the volume of telephone or face-to-face consulting between 2019 and 2020. positive comments from staff and patients. 27 28 Our ndings suggest that part of the reason for the low proportion in general practice could be the relatively limited usefulness of video-consultations over telephone or face-to-face in the majority of circumstances.…”
Section: Comparison With the Literaturementioning
confidence: 48%
See 1 more Smart Citation
“…The cross-sectional RSC study found more remote consulting amongst people in IMD quintile 1 (most deprived). 4 In our longitudinal study, we found no signi cant effect of deprivation on the change in the volume of telephone or face-to-face consulting between 2019 and 2020. positive comments from staff and patients. 27 28 Our ndings suggest that part of the reason for the low proportion in general practice could be the relatively limited usefulness of video-consultations over telephone or face-to-face in the majority of circumstances.…”
Section: Comparison With the Literaturementioning
confidence: 48%
“…2 Online or telephone triage models were introduced, 3 with most triaged consultations done via telephone or video. 4 This change was possible because much of the infrastructure was already established. The UK is a global leader in alternatives to face-to-face primary care consultations, and the NHS long-term plan committed practices to offer online consultations (e-consultations) from April 2020 and video from April 2021.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely acknowledged that objective data (such as that obtained using accelerometers or pedometers) has higher validity than self-estimation of sedentary behaviour and physical activity, with self-estimation shown to typically underestimate sedentary behaviour by approximately 1.74 h per day [ 45 , 46 , 50 ]. With the recent increase in remote consulting among GPs as a result of the COVID-19 pandemic, GPs have less face-to-face interaction with patients, with the majority of consultations now happening via telephone and video [ 51 ]. This opens up both challenges and opportunities for GPs regarding their levels of sedentary behaviour [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study found that within resource-rich settings and consistent access to a regular primary care physician prior to the pandemic, in-person outpatient visits for chronic conditions fell by 60% to 70%, while there was a 60% to 100% increase in video and telephone consultations. 16 This smooth shift into remote care resulted in higher patient satisfaction and consistent no-show rates than before the onset of COVID-19, reflecting these patients continued timely and effective access to primary care during the COVID-19 pandemic. 16 , 17 However, even in resource-rich settings, there is a high degree of variability among different communities; 18 specifically, inequalities in chronic diseases and the social determinants of health among minority ethnic groups, people living in areas of higher socioeconomic deprivation, individuals living in poverty, and other marginalised groups.…”
Section: Healthcare Characteristics and Utilization By Individuals Wimentioning
confidence: 97%